A BIBLIOMETRIC REVIEW OF PROCESS MINING IN MANUFACTURING PROCESSES - Gomes da Silva, Ramon (Revista Latino-Americana de Inovação e Engenharia de Produção, 2019)
The process mining is essential when it is needed to know what is happening in the execution of the processes, even more when it is manufacturing processes. Also, there is a lack of studies on process mining in manufacturing processes, one reason is because the process mining still a young field of study. Therefore, this paper presents a bibliometric review of a history of the process mining techniques applied in manufacturing processes. It was used, as methodology, a systematic review of the literature, by consulting databases from Web of Science and Scopus, using filters to generate a sample that would match with the scope of the research. As results, it was made some analysis, which presents the identification of the years, authors, research source, countries, number of citations, keywords cloud and industry type used in the cases studied. Also, some graphics, tables and information are presented on this paper.